Modeling and problem solving techniques for engineers - Horváth, László (Elsevier Academic Press, 2004)
"Today, the majority of engineers in many varied fields must utilize CAD/CAM systems in their work, but due to the increasing number and sophistication of programs and methods available, no one engineer can possibly be an expert in all of them. This book will help, by offering a detailed and comprehensive survey of all the leading computer-aided engineering methods, effectively providing a map to this sometimes confusing world. It is especially written for design and production engineers practicing in the modern industrial environment, where design, analysis, manufacturing planning, production planning and computer controlled equipment programming are all governed by CAD/CAM systems. The authors, who are engineering professors as well as IT professionals, clearly explain concepts, approaches, principles, and practical methods in purposefully IT-jargon free language, so that engineers will not get lost in a tangle of acronyms. It profides basic theoretical background and examines the relative value of various competitive computer-aided engineering methods, so that engineers will feel confident in making design tool choices, without having to become specialists in the development issues surrounding each system"--Back cover.